Synthesis and Electro-Optical Evaluation of 2,6-Bis(arylethynyl)anthraquinones - Tumuluri, Anusha; Khanna, Bhanupriya; Altalib, Ammar; D. Revell, Kevin (Letters in Organic Chemistry, 2015)
A series of 2,6-bis(arylethynyl)anthraquinones was prepared via double Sonogashira coupling to 2,6-diiodoanthraquinone, and characterized with regard to their optical and electronic properties. Substitution with a derivatized phenylethynyl group produced a λonset of 366 nm (Eg = 3.4 eV), but the more highly conjugated 2,6-bis(9’-anthracylethynyl)anthraquinones exhibited a λonset of approximately 540 nm (Eg = 2.3 eV). Poor solubility in the unsubstituted 9’-anthracylethynyl system hampered complete characterization or purification, but the 10’-hexanoylanthrac-9’-ylethynyl analog exhibited significantly better solubility. The preparation of several other functionalized derivatives was also explored, and key synthetic findings are reported.
Keywords: sonogashira coupling